The crosstalk between nitrate signaling and other signaling molecules in Arabidopsis thaliana - Mao, Jingjing; Tian, Zhen; Sun, Jinhao; Wang, Duanfei; Yu, Yating; Li, Shaopeng (Frontiers in Plant Science, 2025)
Nitrate signaling coordinates the expression of a broad range of genes involved in nitrate uptake, transport, and assimilation, playing a crucial role in plant growth and development. Notably, nitrate signaling interacts extensively with various messenger molecules, including phytohormones, calcium ions (Ca2+), reactive oxygen species (ROS), peptides, and sucrose. This crosstalk amplifies nitrate signaling and optimizes nutrient uptake, coordinating developmental processes and enhancing stress tolerance. Understanding the interactions between nitrate and these signaling molecules offers valuable insights into improving crop nutrient use efficiency (NUE), stress resilience, and agricultural sustainability. Using Arabidopsis thaliana as a model, this review consolidates current knowledge on nitrate signaling and its interplay with other signaling pathways that regulate plant development and adaptation. Finally, the review highlights potential genetic strategies for enhancing NUE, contributing to more sustainable agricultural practices.